Invest Outside the Box Understanding Different Asset Classes and Strategies - Dennison, Tariq (Springer Singapore, 2018)
"I give this book to my sales, trading, and legal teams as a great foundation to build market and product knowledge" -Bill Bamber, Managing Director, Structured Investment Products, Canadian Imperial Bank of Commerce (CIBC) "An excellent logical and explanatory guide to the assets and strategies available to investors globally" -Emanuel Derman, Columbia University This book is a practical and concise guide to major asset classes, investment strategies, and foreign markets. For investors familiar with one "box" of investments, this book serves as a non-technical introduction to other "boxes" worth diversifying into, such as bonds, real estate, private equity, cryptocurrencies, and Chinese A-shares. Readers with no prior finance background will find this book an accessible entry point to investing. Written by a practitioner, this volume can serve as course material for introductory investing classes or as an on-the-job guidebook for professionals and practicing investors. Tariq Dennison is a Hong Kong based fund manager and pension advisor investing retirement accounts across global stock, bond, and alternatives markets. An American raised in Europe and long resident in Asia, Tariq has a lifelong natural interest in interest rates, foreign currencies, and frontier and out-of-favor markets. He has worked at Accenture, Commerzbank, Bear Stearns, J.P. Morgan, CIBC, and Société Générale in San Francisco, New York, Toronto, London and Hong Kong, before starting GFM Asset Management in 2014. Tariq teaches fixed income and alternative investments at ESSEC Business School in Singapore, CFA Singapore, and the Hong Kong Society of Financial Analysts, and holds a Bachelor's degree from Marquette University and a Master's in Financial Engineering from the University of California at Berkeley's Haas School of Business.